TEACHER'S STRATEGIES AND CHALLENGES TO ENHANCE STUDENTS' CRITICAL THINKING IN ESP CLASSROOM: A TALK-IN-INTERACTION ANALYSIS - GILANG RAJASA, - (2018)
Pada abad 21 ini, banyak informasi tersedia secara online. Ini sebagian besar diakses oleh orang muda termasuk mahasiswa. Namun, tidak semua informasi dapat diandalkan bahwa pengguna harus memilih sumber yang relevan dan berguna untuk kehidupan mereka. Sayangnya, keterampilan untuk menyaring informasi ini tidak secara otomatis diberikan tetapi harus dipelajari. Mengadopsi pemikiran kritis Elder dan Paul (1994), penelitian ini bertujuan untuk mengungkapkan strategi dan tantangan guru dalam memfasilitasi pemikiran kritis siswa di kelas ESP. Dalam studi kualitatif deskriptif ini, seorang guru sarjana dipilih secara khusus untuk menjadi peserta tunggal. Observasi kelas, wawancara, dan analisis dokumen digunakan sebagai alat untuk memperoleh informasi yang dibutuhkan. Talk-in-interaksi Yule (1999) disajikan untuk menganalisis percakapan guru-siswa. Analisis menghasilkan tiga strategi utama dalam meningkatkan pemikiran kritis siswa (debat mini, diskusi ulasan film, dan diskusi rekan). Beberapa tantangan, bagaimanapun, terjadi di sepanjang penerapan strategi pengajaran berpikir kritis. Oleh karena itu, mengembangkan set strategi pengajaran harus dipertimbangkan untuk mengurangi hambatan pada peningkatan siswa. Rekomendasi untuk studi lebih lanjut juga disajikan dan didiskusikan;---In this 21st century, a lot of information is available online. It is mostly accessed by young people including university students. However, not all information is reliable that users have to select relevant and useful sources for their life. Unfortunately, this skill for screening information is not automatically given, but should be learned. Adopting Elder and Paul's (1994) critical thinking, the present study is aimed at revealing teacher's strategies and challenges in facilitating students' critical thinking in an ESP classroom. In this descriptive qualitative study, an undergraduate teacher was selected purposefully to be the single participant. Classroom observation, interview, and document analysis were used as tools to gain information needed. Yule's (1999) talk-in-interaction was presented to analyze the teacher-students conversation. The analysis resulted in three main strategies in enhancing students' critical thinking (mini debate, movie review discussion, and peer discussion). Some challenges, however, occurred along the implementation of critical thinking teaching strategies. Therefore, developing sets of teaching strategies should be taken into consideration to reduce the impediments on the students' enhancement. Recommendations for further studies are also presented and discussed.